Sepsis, a Common Endpoint to Even Non-Infectious Comorbidities, A Single Center Study on 49,107 Patients, at a Tertiary Care Center in India (Indian Journal of Public Health Research & Development, 2021)
Background & Objectives- Sepsis, is caused by dysregulated host response that leads to multiple organdysfunction. Complications of sepsis being so grave, it becomes important to address it in a communitysetting as sepsis always presents itself as a reason for clinical deterioration of preventable and commondiseases.Methods- Analysis of in-patient records of 49,107 at a tertiary care centre in India were analysed fromyears 2016-2020, to study correlation of sepsis with various comorbidities such as Diabetes, Hypertension,Coronary artery disease, Cerebrovascular accident and Thyroid; and also, to study the death toll occurringdue to sepsis.Results- Sepsis has a higher prevalence in the vulnerable age groups that is > 60 years followed by < 20years of age. Sepsis is observed more in males (56.32%) than females (43.68%). Sepsis was found to havea statistically significant association (P
Keywords: Cerebrovascular accident, Coronary artery disease, Diabetes, Hypertension, infection, sepsis, septic shock, Thyroid.